Monitoring aging of hen egg by integrated quantitative peptidomic procedures. (February 2021) - Renzone, Giovanni; Novi, Gianfranco; Scaloni, Andrea; Arena, Simona
Graphical abstract: Highlights: Molecular aging can determine important changes in the functions and properties of egg compartments. Integrated peptidomic procedures allowed to identify peptide markers of egg aging. Untargeted label-free quantitation identified 30 and 66 aging markers in egg white and yolk plasma. Selected molecules were validated through a targeted parallel reaction monitoring procedure. Quantitative results reflected physicochemical phenomena occurring in egg during storage. Abstract: Environmental conditions and timing of egg storage highly affect raw material quality. Aging and endogenous processing of constituent proteins can determine important changes in specific functions and technological properties of inner egg compartments. We here used integrated peptidomic procedures to identify peptide markers of egg freshness. At first, peptides extracted from egg white and yolk plasma taken from eggs stored for different times were subjected to a label-free untargeted quantitation procedure based on nanoLC-ESI-Q-Orbitrap-MS/MS, which identified 836 and 1974 unique variable molecules, respectively. By applying stringent criteria for filtering data, 30 and 66 putative egg aging markers were selected for egg white and yolk plasma, respectively. Proposed molecules were then validated through a targeted label-free parallel reaction monitoring procedure based on nanoLC-ESI-Q-Orbitrap-MS/MS, confirming quantitative trends for 19 and 25 peptides in egg white and yolk plasma, respectively, and generating a robust panel of egg storage markers. Quantitative results reflected physico-chemical phenomena occurring in egg compartments during storage and offered essential information for the development of novel control procedures to assess quality features of fresh/stored raw material.